Our Day Out - Russell, Willy (Reed Educational & Professioal Publishing Ltd, 1993)
Willy Russell's popular television play is a witty, fast-moving drama. The progress class is on a trip to Wales where liberal Mrs Kay and strict Mr Briggs have completely different ideas about how the day should be organised$1! =s
Keywords: Plays